Feeding and food relations of mass species of sculpins (Cottidae, Pisces) in Peter the Great Bay (Japan Sea) in summer - Olga I. Pushchina; Sergey F. Solomatov; Pavel V. Kalchugin; Ludmila L. Budnikova (Известия ТИНРО, 2016)
Feeding and competitive relationships are considered qualitatively and quantitatively for 9 common species of sculpins (Cottidae) on the data of bottom-trawl surveys of the shelf and upper continental slope of Peter the Great Bay conducted in June-September of 2002-2009. Most of these species are facultative predators (elkhorn sculpin Alcichthys elongatus , blackedged sculpin Gymnocanthus herzensteini , plain sculpin Myoxocephalus jaok , snowy sculpin M. brandti , and great sculpin M. polyacanthocephalus ), two of them are euryphages (thorny sculpin Icelus cataphractus and graypurple sculpin G. detrisus ), and two other are benthophages (antlered sculpin Enophrys diceraus is benthophagous polyphage and thread sculpin G. pistilliger is benthofagous worm-feeder). Daily ration of these species is estimated as 2.4-3.6 % of body weight, with exception of antlered sculpin that is distinguished by lower feeding intensity (on average 1.0 % per day) due to features of its physiology. Food competition between sculpins is estimated as very low, at least in summer feeding season. Cases of significant overlapping of trophic niches noted for the predatory species, as common consumption of echiuran Echiurus echiurus and snow crab Chionoecetes opilio , are reasoned by high abundance and availability of these prey, not by real competition.